MASALAH-MASALAH SOSIAL DALAM KUMPULAN CERPEN BIUR KARYA DJELANTIK SANTHA - Aristia Ulandari, Ni Putu (Humanis; Volume 11. No 1. April 2015)
This study discusses about structure and social problems that exist in the collection of short stories entitled Biur made by Djeantik Santha. This analysis using structural and sociology theory. This study to describe the structure an social problems in that collection of short stories. To simplify the anaslysis method used in the provision of data phase is listen and note. Used also anaslysis method with interviews with recording techniques and note the interviews. The next stage of data analysis using descriptive qualitative as well as quantitative methods supported by. In this stage also with descriptive analytic techniues. And last stage of data analysis using formal methods informally assisted with inductive deductive thinking patterns. The results of this study indicate that: (1) structural analysis of the incident, plot (consisting of forward flow and flow back and forth), figure and character (physiological, sosiological, and psychological), background (time, place, feel), theme including: karmaphalas, beliefs in the search for God, an forbidden relationship, the struggle of a mother, a family meeting and parting, and mandate (2) social problems based on the cutomary law of Bali including Kulkul Bulus is gong sound very fast, astra is children born outside of legal marriage, caste father and sudras mother, a forced marriage, covert, a forbidden marriage with family, widow, and mixed marriages.
Keywords: collection, short story, social problem, stucture